River health assessment based on set pair analysis model in typical Northern Chinese City - Bu, Jiuhe; Wang, Tao; Xu, Tian (Frontiers in Ecology and Evolution, 2025)
Rivers are critical to ecological and societal sustainability, yet human activities like urbanization, industrialization, and agricultural runoff increasingly threaten their ecological health. This study investigates the ecological health of six major rivers in Dalian City, China, focusing on the relationships between aquatic biological communities and environmental factors. A total of 168 phytoplankton species, 110 zooplankton species, and 102 macrozoobenthos species were identified. The key environmental factors influencing these communities included pH, dissolved oxygen, ammonium nitrogen, total phosphorus, and altitude. Using an entropy-weighted set pair analysis model, spatial variations in river ecosystem health were evaluated. Monitoring sites S12 and S15 exhibited good health conditions, while sites S4, S8, and S17 were rated as poor (Grade IV), and S7 was severely polluted (Grade V). Other sites showed borderline health (Grade III). This research provides valuable insights for improving river ecosystem management and biodiversity conservation in Dalian City, offering a scientific basis for addressing water quality and ecological challenges.